2012
DOI: 10.4314/njp.v39i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of mother's touch in assessing the presence of fever in children

Abstract: Abstract:Background: Fever is a very common presenting complaint in children and is of great diagnostic importance. The presence of fever in a child which is often determined by tactile assessment is a major source of concern to caregivers necessitating either the use of medications and /or hospital visitation. Objective: To test the reliability of tactile assessment of fever by mothers and to ascertain if palpation of a single site or multiple sites affects the accuracy. Method: The study was conducted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
0
5
1
6
Order By: Relevance
“…Studies have found that although the temperature assessment by palpation is good enough to detect fever (sensitivity 89.2 to 96.3% and specificity 23 to 64.3%), the assessment is influenced by subjectivity, technique, and environmental factors. [8][9][10][11] Banco et al reported that detection of fever by mothers without using a thermometer had a sensitivity of 73.9% and a specificity of 85.6%. 12 As many as 90% of children aged ≤ 2 years with temperature ≥ 38.9˚C were diagnosed as having fever, and 52.3% of children who complained of suffering from a fever were actually proven to have fever when the temperature measurement was taken with thermometer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that although the temperature assessment by palpation is good enough to detect fever (sensitivity 89.2 to 96.3% and specificity 23 to 64.3%), the assessment is influenced by subjectivity, technique, and environmental factors. [8][9][10][11] Banco et al reported that detection of fever by mothers without using a thermometer had a sensitivity of 73.9% and a specificity of 85.6%. 12 As many as 90% of children aged ≤ 2 years with temperature ≥ 38.9˚C were diagnosed as having fever, and 52.3% of children who complained of suffering from a fever were actually proven to have fever when the temperature measurement was taken with thermometer.…”
Section: Discussionmentioning
confidence: 99%
“…Najpowszechniejsze miejsca takiej oceny to brzuch (34,5%) i czoło (31-28,0%), szyja (19,5), klatka piersiowa (14%), ręce (4,5%) [16,17], najrzadziej jest to pachwina (0,5%) [17]. Za najlepsze miejsca uznano brzuch, szyję i czoło [16].…”
Section: Wprowadzenieunclassified
“…Za najlepsze miejsca uznano brzuch, szyję i czoło [16]. Należy jednak zauważyć, że ubranie lub odsłonięcie określonych części ciała, poddanie ich działaniu niskiej (okłady) lub wysokiej (przykrycie) temperatury może mieć znaczenie dla trafności ceny [17]. Dotyk w kilku różnych miejscach może wpływać na trafność oceny [18], chociaż w szeroko zakrojonych badaniach nie potwierdzono takiego związku [17].…”
Section: Wprowadzenieunclassified
See 2 more Smart Citations